Collapse and recovery of forage fish populations prior to commercial exploitation. Issue 4 (22nd February 2017) - McClatchie, S.; Hendy, I. L.; Thompson, A. R.; Watson, W.
Abstract: We use a new, well‐calibrated 500 year paleorecord off southern California to determine collapse frequency, cross correlation, persistence, and return times of exploited forage fish populations. The paleorecord shows that "collapse" (defined as <10% of the mean peak biomass) is a normal state repeatedly experienced by northern anchovy, Pacific hake, and Pacific sardine which were collapsed 29–40% of the time, prior to commercial fishing exploitation. Mean (± SD) persistence of "fishable biomass" (defined as one third mean peak biomass from the paleorecord) was 19 ± 18, 15 ± 17, and 12 ± 7 years for anchovy, hake, and sardine. Mean return times to the same biomass was 8 years for anchovy but 22 years for sardine and hake. Further, we find that sardine and anchovy are positively correlated over 400 years, consistent with coherent declines of both species off California. Persistence and return times combined with positive sardine‐anchovy correlation indicate that on average 1–2 decades of fishable biomass will be followed by 1–2 decades of low forage. Forage populations are resilient on the 500 year time scale, but their collapse and recovery cycle (based on the paleorecord) are suited to alternating periods of high fishing mortality and periods of little or no fishing. Key Points: The paleorecord shows that "collapse" is a normal state repeatedly experienced by northern anchovy, Pacific hake, and Pacific sardine Mean return times to "fishable" biomass was 8 years for anchovy, but 22 years for sardine and hake, and persistence was of the same order Sardine and anchovy are positively correlated over 400 years, consistent with coherent declines of both species off California